Application of distributive justice theory to the CEO pay problem: Recommendations for reform - Wilhelm, Paul G. (Journal of business ethics, 1993)
An ethical analysis of chief executive officer (CEO) salaries can be approached via theory on distributive justice and an examination of some corporate codes of ethics. U.S. CEO salaries are compared with their Japanese and European counterparts, and factors behind the high U.S. CEO salaries are reviewed. The negative repercussions of high pay are discussed, including feelings of unfairness, declining morale and greater cynicism found in lower level employees. Reduced research and development budgets, and downsized organizations are related to the maintenance of high CEO salaries. After considering economic repercussions, recommendations for reform, which lead to the greatest expected benefit of the least advantaged, are made.